Correlation between Loss of Cervical Lordosis and Degenerative Diseases of the Sub-axial Cervical Spine Columns - Martadiani, Elysanti Dwi; Asih, Made Widhi; Laksminigsih, Nyoman Srie; Tjan, Anastasia; Widyasari, Nyoman (Bali medical journal, 2019)
Background: Subaxial cervical spine is the cervical segment which commonly undergo degenerative changes. There are numerous cervical lordosis angle measurement, however posterior tangential method is considered more accurate to detect any degenerative related changes.Aim: This study aimed to find the profile of cervical lordotic curve among patients with cervical degenerative disease, and to determine the correlation between degenerative process of subaxial cervical spine columns and cervical curve malalignment.Method: A cross sectional study was conducted by adopting the posterior tangent measurement. Cervical alignment was measured from cervical MRI mid sagittal section to identify loss of cervical lordotic and the presence of kyphosis. Degenerative disease of each vertebral column of subaxial cervical spine, anterior and posterior were evaluated. Spearman correlation test was done to identify the relationship between degenerative process of each column of subaxial cervical spine with loss of cervical lordosis and the presence of kyphosis. Multivariate analysis was done to adjust the effect of confounding variable.Result: Total of 90 subjects with male predominance (62%), mean age 54Â± 1.3 years. Neck pain contributes the most presenting complain (92%). As many as 51 subjects have hypo-lordosis, while 32 subjects have kyphotic changes. There was no significant correlation between degenerative process of each column of subaxial cervical spine and loss of cervical lordotic, but significant correlation was found between posterior listhesis and cervical kyphosis defomity. (p < 0.05).Conclusion: There was significant correlation between cervical kyphotic malalignment with posterior listheis Â in all three vertebra columns instead of hypo-lordosis.